The Application of Art Therapy as a Medium for Self-Expression in Managing Emotions among Grade XII MIPA 1 Students at MAN 1 Tuban - A. Musthofa Kamal; Pudji Rahmawati (AMK : Abdi Masyarakat UIKA, 2026)
This study aims to describe the application of Art Therapy as a medium of self-expression in helping 12th-grade MIPA 1 students of MAN 1 Tuban manage their emotions. The research approach uses a qualitative method with an action research type that is carried out in three stages, namely planning, implementation, and reflection. The research subjects were 12th-grade MIPA 1 students who experienced difficulties in expressing and controlling emotions. Data were collected through observation, interviews, and documentation, then analyzed using reduction, presentation, and conclusion drawing techniques. The results of the study indicate that the application of Art Therapy through drawing activities has a positive impact on students' abilities to recognize, express, and control emotions. Students become more open, confident, and able to channel negative feelings constructively. In addition, this activity creates a more comfortable and reflective learning atmosphere. Thus, Art Therapy is proven to be effective as an alternative medium in managing emotions and developing students' psychological well-being in the school environment